Barack Obama and the Calculus of Presidential Ambiguity. (September 2013) - Foley, Michael
The 2008 US presidential election brought victory to a largely inexperienced and untested politician who had offered himself as both a symbolic register of social change and an agency of transformative action. President Obama's campaign for re-election in 2012 prompted an intensive period of retrospection and reassessment into what the preceding four years had revealed about both the Obama phenomenon and the complex systemic environment with which he had to engage. Using an array of recently published overviews, the article examines the Obama Presidency from three different categories of analytical and evaluative assessment. It proceeds to review the seminal complaints made against his policies and style from both ends of the political spectrum – as well as Obama's responses to the increasingly fractious nature of the positioning strategies undertaken by his opponents. Finally, observations are made concerning a series of interpretive issues surrounding the 2012 result and its implications for Obama's reputation and legacy.